The effect of trade opening and direct foreign investment on Perú’s economic growth, 2007-2016 - Valdez Roca, Alvaro Fernando (2018)
The main objective of this explicative research was to determine the effect of trade opening and direct foreign investment on Peruvian economic growth, 2007-2016. This research was developed inside one non-experimental and longitudinal design; The sample was constituted by data related to study variables during the period 2007-2016 and collected from reports prepared by BCRP, INEI and Proinversion; furthermore, it was used a convenience sampling; the validity of regression models was realized through analysis of variance. This research concluded that, in peruvian case, only trade opening affected significatly on growth rate of real GDP per capita during the period 2007-2016 explaining more than fifty percent of its variation. One suggestion as a product of this research is the design of politics that fosters the trade opening through removing barriers and the search for new trade agreements where the national interests prevail over other types of interests.